ANALISIS KEMAMPUAN KONEKSI MATEMATIKA DAN SELF EFFICACY MATEMATIS SISWA KELAS VII SMP NEGRI 7 NARINGGUL CIANJUR - Lindawati Lindawati (Departement of Mathematics Education, 2019)
Mathematical connection ability is the ability of students to understand the interrelationship between mathematical concepts, the relevance of mathematics with other subjects and the relevance of mathematics to solving problems in everyday life. The method used in this study is a Descriptive Qualitative Method with the aim of analyzing the results of student answers to mathematical connections and self efficacy search questionnaire of SMP 7 Naringgul students in West Cianjur regency. The samples studied were 20 students in class 7 Naringgul, West Cianjur Regency. The test used is a question of mathematical connections as much as 4 questions and non-test questions self esteem is given to each student. The results of the analysis obtained are the mathematical connection ability in high schools in West Bandung district based on written description tests are still relatively low.